2012
DOI: 10.1111/j.1365-2249.2012.04608.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly conserved CDR3 region in circulating CD4+Vβ5+ T cells may be associated with cytotoxic activity in Chagas disease

Abstract: SummaryHuman infection with Trypanosoma cruzi leads to Chagas disease, which presents as several different clinical conditions ranging from an asymptomatic form to a severe dilated cardiomyopathy. Several studies have demonstrated that T cells play a critical role in the development of cardiac pathology, as well as in immunoregulation during chronic disease. However, the mechanisms that drive protective or pathogenic T cell response are not known. We have shown that CD4 + T cells from chagasic patients prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 37 publications
0
20
0
3
Order By: Relevance
“…Moreover, the different tissue tropisms were correlated with different MHC gene expression in the murine host (30). Studies with Chagas patients also suggested that some MHC alleles could be associated with clinical forms of chronic Chagas disease (31, 32). Despite these findings, it is still difficult to establish a relationship between the genetic diversity of parasite and clinical manifestation of human Chagas disease.…”
Section: Chagas Disease: a Complex Host-parasite Interaction Drives Pmentioning
confidence: 99%
“…Moreover, the different tissue tropisms were correlated with different MHC gene expression in the murine host (30). Studies with Chagas patients also suggested that some MHC alleles could be associated with clinical forms of chronic Chagas disease (31, 32). Despite these findings, it is still difficult to establish a relationship between the genetic diversity of parasite and clinical manifestation of human Chagas disease.…”
Section: Chagas Disease: a Complex Host-parasite Interaction Drives Pmentioning
confidence: 99%
“…In this study, we evaluated the influence of single and co‐infection with isolates belonging to DTU TcIV and TcV on the immunological characteristics of human monocytes. TcIV occurs in North and South America and is associated with human Chagas disease in Venezuela and in the Brazilian Amazon . It is speculated that TcIV parasites are responsible for the low parasitemia and morbidity seen in chronic Chagas disease in Amazonas State in Brazil, despite a high seroprevalence .…”
Section: Discussionmentioning
confidence: 99%
“…Nonexcluding hypotheses argue that T‐cell exhaustion is the cause of the severe clinical form of Chagas disease and that the balance between the inflammatory (TNF) and anti‐inflammatory (IL‐10) cytokines is crucial for the clinical outcome . Although T cells from Chagas patients can produce TNF and IL‐10, monocytes are the main source of these cytokines in Chagas disease …”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that human beings have no TCR repertoire deletions compared with mice, during human Chagas disease there is also a differential expression of TCR-Vβ5 T cells from infected patients in different stages of the disease, and preferential expansion of CD4 + Vβ5 + and CD8 + Vβ5 + T cells was also observed when mononuclear cells were exposed in vitro to parasite antigens, suggesting a possible commitment of these cells in the pathology ( 113 ). The preferential expansion of Vβ5 + populations occurs in both CD28 + and CD28 − CD4 + T cell subsets and is related to restricted sequences of CDR3 ( 114 , 115 ). Interestingly, C57BL/6 mice, which do not suffer the clonal deletion of TCR-Vβ cell subsets, also expand peripherally CD8 + Vβ5 + clones during infection ( 112 ).…”
Section: The Intrathymic T-cell Repertoire and Exit Of Potentially Aumentioning
confidence: 99%